Analysis of Financial Statements PT. Hanjaya Mandala Sampoerna TBK - Luthfi Widianto Halim; Rossherleen Clarissa Halim; Imam Setia Permana (Future Science, 2020)
The purpose of this analysis is to know the effect of company profitability on timeliness and effectiveness concerning the progress of a company's financial statements PT. Hanjaya Mandala Sampoerna Tbk from 2016 to 2019. The method used in this research is the quantitative research method and the data obtained in this financial statement is downloaded from the official website of the Indonesia Stock Exchange (IDX). The ratios used are liquidity ratio, solvency ratio, and profitability ratio. Analysis has taken from 2016 to 2019 from liquidity ratio and precisely at the quick ratio, the company was able to pay its short-term debt smoothly despite a decrease in 2019, in previous years the payment of a short-term debt from the company is fairly smooth so that obligations can be met. But from the solvency ratio of the company PT. Hanjaya Mandala Sampoerna Tbk is less effective in managing the company's wealth/assets, proven from year to year because the Debt to Asset Ratio (DAR) is less than 100%. For profitability ratio can be seen from the net profit margin has a value of 13% over 3 years means, the result is more than 10% then the comparison between price and cost has been well set by looking at the profit results obtained.